KAJIAN VISUAL BATIK HOKOKAI PEKALONGAN MOTIF LERENG, BUNGA DAN KUPU - Sutriyanto Sutriyanto; Veronika Kristanti PL (Ornamen, 2014)
Indonesia as the batik center of the world, where the one of them is Pekalongan city in the north coast of thejava island that famed with batik product. Furthermore, Pekalongan is also famed with the openess of influencefrom outside and able to catch out the sesitiveness of social change which embodied in an batik artisticwhether certain patterns and motifs, especially during the Japanese occupation. Japanese nation is a nationthat known as a nation which uphold the arts and culture by nature, where it is visible in Hokokai batik motifthat growing in Pekalongan. Lereng, Bunga, dan Kupu-kupu motifs are reflection from the nature of thatcountry. The emergence of that motif is clearly has a logical and philosophical reasons that those existencedominate the Hokokai batik motif. Besides having a high level of complexity, the Hokokai batik motif alsohas the characteristic of very bright colouration which turn that motif unique. Nowadays, that motif become amainstay of Pekalongan city as high class batik that has own certain market.Keywords: Batik, Motif, Pekalongan